2012
DOI: 10.1093/hmg/dds513
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of associations of APOBEC3B gene deletion with susceptibility to persistent HBV infection and hepatocellular carcinoma

Abstract: APOBEC3s are a family of cytidine deaminases involved in innate cellular immunity against virus including hepatitis B virus (HBV). A germline deletion across APOBEC3A and APOBEC3B (A3B) genes results in complete removal of the A3B coding region and destroys A3B expression. To determine whether this deletion affects susceptibility to HBV infection and HBV-related hepatocellular carcinoma (HCC), A3B genotypes were analyzed in 1124 individuals with HCC, 510 individuals with persistent HBV infection and 826 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 42 publications
1
56
1
Order By: Relevance
“…However, another study implicated APOBEC3A as well as APOBEC3B as possible mutagenic enzymes in breast cancer 77 . Interestingly, APOBEC3B homozygous deletion is polymorphic within the human population 78 and individuals homozygous-null and even heterozygous have a detectable increase in frequencies of breast or liver cancers 79-81 and can show a high frequency of mutations fitting the APOBEC signature 82 . Identification of the real culprit through analysis of cancer genomics datasets is complicated by the level of mutagenesis likely depending on additional factors besides mRNA levels of APOBECs, such as the active protein level, accessibility of chromosomal DNA, availability of ssDNA substrate (discussed in 56 ).…”
Section: Hypermutation In Cancermentioning
confidence: 99%
“…However, another study implicated APOBEC3A as well as APOBEC3B as possible mutagenic enzymes in breast cancer 77 . Interestingly, APOBEC3B homozygous deletion is polymorphic within the human population 78 and individuals homozygous-null and even heterozygous have a detectable increase in frequencies of breast or liver cancers 79-81 and can show a high frequency of mutations fitting the APOBEC signature 82 . Identification of the real culprit through analysis of cancer genomics datasets is complicated by the level of mutagenesis likely depending on additional factors besides mRNA levels of APOBECs, such as the active protein level, accessibility of chromosomal DNA, availability of ssDNA substrate (discussed in 56 ).…”
Section: Hypermutation In Cancermentioning
confidence: 99%
“…These mechanistic findings above tie in well with the recently identified higher mutation burden in breast cancer genomes 27 , indicating that this is causal and not a surrogate marker. They help explain the heterozygous effect between DA3B and cancer [24][25][26][27] . Given the sensitivity of A3A to inflammatory environments involving type I and II interferons, while chronic inflammation has long been associated with the onset of cancer 41 , it is distinctly possible that repeated A3A-induced DNA damage will be a major driving force behind iterative somatic mutation/ selection of the human genome, cutting across many cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…However, the degree of editing, of the order of a few mutations per kilobase, was unlike that observed for A3A (hundreds per kilobase), and probably represents PCR background 22 . The role of A3B in genome editing is intriguing, given that deletion of most of the A3B gene results in a higher odds ratio of developing breast, ovarian or liver cancer [23][24][25][26] . Indeed, complete genome sequencing of DA3B À / À breast cancer genomes revealed a higher than average mutation burden greatly consolidating these genetic studies 27 .…”
mentioning
confidence: 99%
“…Interestingly, a recent genetic study revealed a positive correlation between A3B loss-of-function mutations with increased frequency of HBV persistence. 11 However, the A3B deletion allele did not affect the LTbR activation-induced cccDNA loss in PHH, indicating that the previously ascribed association between A3B deletion and HBV in patients may be due to functions other than the deaminase activity against cccDNA. Further adding to the complexity of the APOBEC3-HBV interaction is a previous report that IFN-a only weakly induces A3B, whose expression did not account for IFN-mediated reduction of HBV encapsidated DNA.…”
Section: Commentmentioning
confidence: 78%